Konsep Memilih Teman yang Baik Menurut Hadis - Haura Alfiyah Nida (Jurnal Riset Agama, 2021)
This study aims to discuss the concept of the hadith of good and bad friends. This research is a qualitative type through literature study with content analysis. The results and discussion include general views about peers, hadith syarah about choosing good friends, and hadith concepts in choosing good friends. The conclusion of the study shows that in choosing friends, one should pay attention to the criteria for good friends and bad friends according to what the Prophet taught in authentic hadith with the concept of parables. This study recommends the importance of choosing good friends in the life of this world and the hereafter.